2007
DOI: 10.2337/db06-0384
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effects of cis-9, trans-11–Conjugated Linoleic Acid May Be Mediated via Anti-Inflammatory Effects in White Adipose Tissue

Abstract: Adipose tissue may be the source of insulin desensitizing proinflammatory molecules that predispose to insulin resistance. This study investigated whether dietary fatty acids could attenuate the proinflammatory insulin-resistant state in obese adipose tissue. The potential antidiabetic effect of cis-9, trans-11-conjugated linoleic acid (c9,t11-CLA) was determined, focusing on the molecular markers of insulin sensitivity and inflammation in adipose tissue of ob/ob C57BL-6 mice. Feeding a c9,t11-CLA-enriched die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
102
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 52 publications
6
102
0
4
Order By: Relevance
“…A striking evidence of our study is, on the other hand, the significant effect of cis-9, trans-11 CLA cheese on inflammatory, haemorheological and platelet aggregation profiles, by possibly hypothesising a beneficial role of this particular isoform of CLA on these pathophysiological processes. CLAs have been previously reported to attenuate inflammatory cytokine expression in animals and humans [18], and it has been recently reported that they are able to inhibit the expression of cytokine-induced adhesion molecules on endothelial and smooth muscle cells [19]. Thus, it is conceivable to hypothesise that CLAs are able to attenuate the atherosclerotic process through inhibition of the initiating inflammatory cytokines, such as those measured in our study, as well as through inhibition of the stress signalling cascades these cytokines elicit.…”
Section: Discussionmentioning
confidence: 99%
“…A striking evidence of our study is, on the other hand, the significant effect of cis-9, trans-11 CLA cheese on inflammatory, haemorheological and platelet aggregation profiles, by possibly hypothesising a beneficial role of this particular isoform of CLA on these pathophysiological processes. CLAs have been previously reported to attenuate inflammatory cytokine expression in animals and humans [18], and it has been recently reported that they are able to inhibit the expression of cytokine-induced adhesion molecules on endothelial and smooth muscle cells [19]. Thus, it is conceivable to hypothesise that CLAs are able to attenuate the atherosclerotic process through inhibition of the initiating inflammatory cytokines, such as those measured in our study, as well as through inhibition of the stress signalling cascades these cytokines elicit.…”
Section: Discussionmentioning
confidence: 99%
“…Humans acquire CLAs 3 through diet from dairy products, ruminant meet, and partially hydrogenated vegetable oils. Most biological actions have been ascribed to cis-9, trans-11-CLA and trans-10, cis-12-CLA, which represent the two predominant isomers found in foods and commercial preparations (5)(6)(7)(8). CLAs (commercial preparations often contain equal amounts of both isomers) have emerged as highly popular food supplements in the Western world to achieve beneficial effects on health such as reduction of body fat gain and increase of muscle mass among many other salutary properties (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…n-3 LC-PUFAs have been shown to influence gene expression in both liver and white adipose tissue to improve metabolic health (Al-Hasani and Joost, 2005) as well as acting as antiinflammatory agents and increasing adiponectin levels, which in turn improve insulin sensitivity (Todoric et al, 2006). CLAs have been reported to influence gene expression in white adipose tissue and to increase and decrease insulin sensitivity and to be both pro-and anti-inflammatory depending on the animal model tested and the isomer used (Chung et al, 2005, Wargent et al, 2005Poirier et al, 2006;Moloney et al, 2007;Zhou et al, 2008). Although the design of this study and the relatively small sample size meant that comparisons within the same volunteer, that is the effect of CLA/n-3 PUFA vs control oil supplementation, had greater statistical power than comparisons between volunteers, that is age vs adiposity, the results indicate that both adiposity and age are also factors that may modulate the effects of these dietary fatty acids in humans.…”
Section: Discussionmentioning
confidence: 99%